The Traits of Efficacious and Inefficacious EFL Teachers Based on Students’ Insight - Rahmawansyah Sahib; Nasrullah Nasrullah; Nina Arfiani (JELITA, 2020)
This research aimed at (i) probing traits of efficacious EFL teachers based on students’ insight; (ii) delving traits of inefficacious EFL teachers based on students’ insight; (iii) finding out students’ different experiences on efficacious and inefficacious EFL teachers. This qualitative research used constructivism approach in gaining data and applied coding method in data analysis. The research subjects were 15 students of SMKK Dr. Wahidin Makassar. Five of them were interviewed to gain a deeper explanation about their experiences on the traits of efficacious and inefficacious teachers. The results indicated that built upon the students’ insight (i) the traits of efficacious EFL teachers are having pleasant figure, responsive, mastering the subject taught, promoting students to learn, mastering teaching and learning strategies, able to create a good relation, and performing a good appearance; (ii) inefficacious EFL teachers are indicated by having unpleasant behavior, lack of ability in presenting materials, not supporting students to learn, not mastering teaching strategies, and discriminating; (iii) there is different experience about the traits of efficacious and inefficacious EFL teachers namely teaching based on the textbook only. Some students perceived it was effective for elementary school students, while others perceived it was ineffective for senior high school students.